Gait analysis in the early stage of Parkinson’s disease with a machine learning approach - Yin, Wenchao; Zhu, Wencheng; Gao, Hong; Niu, Xiaohui; Shen, Chenxin; Fan, Xiangmin; Wang, Cui (Frontiers in Neurology, 2024)
Background Gait disorder is a prominent motor symptom in Parkinson’s disease (PD), objective and quantitative assessment of gait is essential for diagnosing and treating PD, particularly in its early stage. Methods This study utilized a non-contact gait assessment system to investigate gait characteristics between individuals with PD and healthy controls, with a focus on early-stage PD. Additionally, we trained two machine learning models to differentiate early-stage PD patients from controls and to predict MDS-UPDRS III score. Results Early-stage PD patients demonstrated reduced stride length, decreased gait speed, slower stride and swing speeds, extended turning time, and reduced cadence compared to controls. Our model, after an integrated analysis of gait parameters, accurately identified early-stage PD patients. Moreover, the model indicated that gait parameters could predict the MDS-UPDRS III score using a machine learning regression approach. Conclusion The non-contact gait assessment system facilitates the objective and quantitative evaluation of gait disorder in PD patients, effectively distinguishing those in the early stage from healthy individuals. The system holds significant potential for the early detection of PD. It also harnesses gait parameters for a reasoned prediction of the MDS-UPDRS III score, thereby quantifying disease severity. Overall, gait assessment is a valuable method for the early identification and ongoing monitoring of PD.